INOVASI PERANCANGAN KOTA - Qomarun Qomarun (Universitas Negeri Yogyakarta, 2006)
ABSTRACTThe crowded phenomenon is made in most of the city now. Thecities sustainable grow and develop to be metropolitan, and just,megapolitan. It makes the farm field change to be houses, buildings,roads and other public facilities of the city. Such of that growth will affectthe land can't be returned to be farm field (irreversible process). It is themost easy to grow the city horizontally, but the land have its limitedness.This paper explores some city development, especially on the basis ofland limitation. It is the responsibility of architectural realm on the, increasing of environment qualitiesKey words: crowded, irreversible, land, model